Pengaruh Pemberian Pupuk Urea, Zeolit dan Asam Humat Terhadap Pertumbuhan Bawang Daun (Allium fistulosum L.) dan Perubahan Beberapa Sifat Kimia Tanah Pada Lahan Gambut - Ramadhani, Riko Putra; Ifansyah, Hairil; Kurnain, Ahmad (Agroekotek View, 2024)
Management and utilization of turf soil for cultivation faces several problems such as pH conditions that quite high acidic, and also the fertility in turf soil is quite low. The mixing of Urea Fertilizer with the addition of ameliorant materials such as Zeolite, and Humic Acid was expected to improve the N nutrient status in turf soils to achieve optimal conditions for plants growth to be cultivated on turf soils. The goals of this study was to determine the effect ofapplied Urea Fertilizer, Zeolite and AH-90 on changes in pH, N-Mineral (NH4+    and NO3-),soluble Fe, dry weight, N absorption of Onion plants (Allium fistusolum L.) that planted on turf soils. This study used a completely randomized design (CRD). The experimental factor that applied in this study was Urea Fertilizer within the level 0 kg/ha, 75kg/ha and 100 kg/ha. Zeolite within the level 0 tons/ha and 10 tons/ha. And Humic Acid (AH-90) within the level 0 kg/ha and 10 kg/ha. The result of this study showed that the interaction of treatment (Urea, Zeolite and Humic Acid) had no impact on parameter changes in the pH value of turf soils, N Plant Tissue,and dry weight of onion plants. The addition of Urea was able to increase the Nitrate (NO3-)content in the soil. And Zeolite application can reduce the Ammonium (NH4+) and iron solubilityin turf soil.